Seismically induced kinking in quartz - Bestmann, Michel; Grasemann, Bernhard; Kilian, Rüdiger; Wheeler, John; Morales, Luiz F.G.; Bezold, Andreas; Pennacchioni, Giorgio (Earth and Planetary Science Letters, 2025)
Deformed quartz veins next (1–1.5 m) to an exhumed pseudotachylyte-bearing (i.e. anciently seismic) fault within the Schobergruppe (Austroalpine Crystalline Complex, Eastern Alps) contain intensely kinked quartz grains. The monoclinic symmetry of kink bands is consistent with the dextral slip sense of the fault. Cathodoluminescence images show a very high density of intragranular, sub-planar, lamellae accompanied by nanometre-scale fluid-related porosity visible in electron backscatter orientation contrast. Based on the oscillating orientation variation across subgrain boundaries (misorientation angle 1–9°) these lamellae (oriented (sub)parallel to a rhomb plane and spaced 4–10 µm apart) are identified as short-wavelength undulatory extinction microstructures (SWUE). Transmission electron microscopy reveals a high degree of recovery (low dislocation density) across the SWUE. Only grains with SWUE oriented parallel to the vein boundary are kinked. Based on detailed microstructural and crystallographic analysis, we infer the following history of kinking evolution related to the seismic cycle: (I) Deformation lamellae formed at high differential stresses preceding, or associated with, seismic rupture propagation. The initial high dislocation density within deformation lamellae provided the mechanical anisotropy in quartz required for (II) the subsequent coseismic initiation of kinking. The lamellae acted as a geometric filter that only allowed r < a> slip of dislocations parallel to the lamellae. These athermal dislocations were able to glide fast over a relatively large distance before piling up and initiating kinking during the coseismic event. Progressive build-up of dislocations resulted in deformation bands which accumulated the final misorientation angle between host domain and kink domain. (III) Residual stress during post-seismic deformation induced dynamic re-arrangement of dislocations into sub-parallel subgrain boundaries which now characterize the kink band boundary region. We suggest that kinking in quartz potentially indicates coseismic deformation and is an important mechanism for incipient strain accommodation during high strain rates.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Anisotropy; Athermal dislocation; Kinking; Quartz; Seismic; Weighted burgers vector